2013
DOI: 10.1021/es403556e
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gas- and Particle-Phase Emissions and Secondary Organic Aerosol Production from Gasoline and Diesel Off-Road Engines

Abstract: Dilution and smog chamber experiments were performed to characterize the primary emissions and secondary organic aerosol (SOA) formation from gasoline and diesel small off-road engines (SOREs). These engines are high emitters of primary gas- and particle-phase pollutants relative to their fuel consumption. Two- and 4-stroke gasoline SOREs emit much more (up to 3 orders of magnitude more) nonmethane organic gases (NMOGs), primary PM and organic carbon than newer on-road gasoline vehicles (per kg of fuel burned)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 44 publications
(87 reference statements)
3
84
1
1
Order By: Relevance
“…The number of possible structural isomers increases exponentially with carbon number (Goldstein and Galbally, 2007) and beyond around C 9 it becomes impossible to accurately identify the structure of every hydrocarbon present in air. Using the retention behaviour of each compound on chromatographic columns it is however possible to assign individual species to particular chemical classes and functionalities.…”
Section: R Dunmore Et Al: Diesel-related Hydrocarbons Can Dominate mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of possible structural isomers increases exponentially with carbon number (Goldstein and Galbally, 2007) and beyond around C 9 it becomes impossible to accurately identify the structure of every hydrocarbon present in air. Using the retention behaviour of each compound on chromatographic columns it is however possible to assign individual species to particular chemical classes and functionalities.…”
Section: R Dunmore Et Al: Diesel-related Hydrocarbons Can Dominate mentioning
confidence: 99%
“…Several recent field studies have investigated the relative importance of gasoline, diesel and biogenic emissions in generating SOA (Gentner et al, 2012;Bahreini et al, 2012;Gordon et al, 2013;Platt et al, 2013;Gordon et al, 2014a, b;Jathar et al, 2014;Ensberg et al, 2014). These have been carried out predominately in the US, particularly in California, where current diesel usage is rather low by global standards.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of organic matter in ambient aerosol have focused on anthropogenic emissions of gasoline, diesel (Gordon et al, 2013;Jathar et al, 2013;Gentner et al, 2012;Bahreini et al, 2012), motor oil (Worton et al, 2014) and biogenic VOCs Paulot et al, 2009;Froyd et al, 2010) as precursors. For long-chain aliphatics, laboratory experiments and simulations have demonstrated substantial contribution of organic nitrates in the resulting particulate matter (Jordan et al, 2008;Lim and Ziemann, 2009;Matsunaga and Ziemann, 2010), but there exist few field observations capable of assessing whether these mechanisms are representative of the ambient processes.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the on-road sector, which has more well-characterized speciated emission data (EPA, 2008(EPA, , 2013Khalek et al, 2009). Our review found that many nonroad engine studies that have speciation data are for older technology engines, based on testing with fuels that are no longer representative of most of the market (Gabele, 1997;EPA, 2004;Volckens et al, 2008), or based on fuels that have never been widely used (Gordon et al, 2013;MargaraGomez et al, 2012;Chai et al, 2013;Zhang and Balasubramanian, 2014). One federal test program reviewed did not have full speciation needed to develop exhaust gas speciation profiles (National Renewable Energy Laboratory [NREL] and Oak Ridge National Laboratory [ORNL], 2009).…”
Section: Introductionmentioning
confidence: 94%